Non-drainage Offers Faster Proprioceptive and Functional Recovery, and More Clinical Benefits for Patients following Primary Total Knee Arthroplasty Compared to Drainage - Unver, Bayram; Eymir, Musa; Karatosun, Vasfi (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
Background Although a non-drainage procedure following total knee arthroplasty (TKA) is becoming more acceptable in enhanced recovery after surgery, postoperative drainage is still commonly used in TKA surgeries. This study aimed to compare the non-drainage to the drainage during the early postoperative stage regarding proprioceptive and functional recovery, and postoperative outcomes of TKA patients.Material and Methods A prospective, single-blind, randomized, controlled trial was carried out on 91 TKA patients, who were randomly allocated into the non-drainage group (NDG) or the drainage group (DG). Patients were evaluated regarding knee proprioception, functional outcomes, pain intensity, range of motion, knee circumference, and anesthetic consumption. Outcomes were assessed at the time of charge, at postoperative 7th day, and at postoperative 3rd month.Results There were no differences between groups at baseline (p > 0.05). During the inpatient period, the NDG experienced superior pain relief (p < 0.05), had a higher Hospital for Special Surgery knee score (p = 0.001), demanded lower assistance from a sitting position to a standing position (p = 0.001) and walking for 4.5 m (p = 0.034), and performed the Timed Up and Go test in a shorter duration (p = 0.016) compared to the DG. The NDG gained the actively straight leg raise earlier (p = 0.009), needed lower anesthetic consumption (p < 0.05), and showed improved proprioception (p < 0.05) compared to the DG during the inpatient period.Conclusions Our findings support that a non-drainage procedure would be a better option to provide a faster proprioceptive and functional recovery, and beneficial results for patients following TKA. Therefore, the non-drainage procedure should be the first choice in TKA surgery rather than drainage.
Keywords: proprioception; functional outcomes; drainage; non-drainage; total knee arthroplasty